2011
DOI: 10.1007/s10815-010-9525-1
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced nucleus DNA fragmentation

Abstract: Purpose The present study was designed to investigate the impact of pressure on nuclear DNA integrity in viable cells of mouse blastocysts. Methods The blastocysts of hybrid F1 females [(C57Bl/10 J × CBA-H);N=15] aged 2-3 months were exposed into the pressure impulse lasting~0.021 s and characterized by a positive pressure peak of~76 mmHg. The nuclear DNA fragmentation index of mouse blastocysts was assessed by TUNEL assay within 60 s after exposure to pressure impulse. Results The mean nuclear DNA fragmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…Therefore, the ET at the early stages of embryo development seems to be more favorable to the embryo viability than its later counterpart, unless the pressure-based catheters are used. The results of the present and the previous experiments demonstrated that the physical conditions created during ET are able to injure vital cell structures (2)(3)(4)11). The application of the microsyringe with a relatively small plunger diameter allowed us to reduce the pressure generated during ET (Fig.…”
Section: Figuresupporting
confidence: 62%
See 1 more Smart Citation
“…Therefore, the ET at the early stages of embryo development seems to be more favorable to the embryo viability than its later counterpart, unless the pressure-based catheters are used. The results of the present and the previous experiments demonstrated that the physical conditions created during ET are able to injure vital cell structures (2)(3)(4)11). The application of the microsyringe with a relatively small plunger diameter allowed us to reduce the pressure generated during ET (Fig.…”
Section: Figuresupporting
confidence: 62%
“…According to recent studies, pressure fluctuations, depending on their magnitude, can cause intracellular enzymes inactivation (8,9), cytoskeletal disorganization (10), and DNA fragmentation (11,12), in addition to influencing cell membranes integrity (13,14) FIGURE 1…”
Section: Discussionmentioning
confidence: 99%
“…With high enough injection speeds, the shear stress can be strong enough to injure the vital cell's organs and impair embryo viability. A recent study indicated that fast ET, with an injection speed of the transferred volume of more than 1 m/sec, could trigger both morphological and apoptotic changes in mouse blastocysts (4,8). Alternatively, reduction of the injection speed to less than 0.1 m/sec allowed to avoid morphological changes and significantly decreased apoptosis in embryos (4).…”
Section: Discussionmentioning
confidence: 99%
“…There are published data pointing out that compression can influence on the nucleus DNA integrity. The fact that even relatively low pressure induce DNA fragmentation was demonstrated in the isolated DNA samples by Schriefer et al and in viable cells of mouse blastocysts by Grygoruk et al DNA fragments after photocatalysis treatment of E. coli cells by TiO 2 NPs was detected by Pigeot-Ŕemy et al Probably, compression of DNA and subsequent destruction of its structure and integrity as a result of TiO 2 NPs action makes it unable to perform its biological functions and is the primary cause of cell death.…”
Section: Resultsmentioning
confidence: 99%